2021
DOI: 10.1177/09576509211026821
|View full text |Cite|
|
Sign up to set email alerts
|

Profile vortex shedding from low-speed axial fan rotor blades: a modelling overview

Abstract: This paper presents an overview of the characteristics potentially influencing the profile vortex shedding (PVS) phenomenon being relevant in noise and vibration of low-speed axial fan rotor blades. Dimensional analysis has been applied to explore the essential dimensionless quantities in a systematic and comprehensive manner. On this basis, limitations have been established, and simplifying assumptions have been set up in terms of PVS investigation. Groups of dimensionless characteristics playing a role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(215 reference statements)
0
2
0
Order By: Relevance
“…Since the cooling fan is one type of axial fan, several investigations also have been concentrated on high-speed axial fans [17], low-speed axial fans [18][19][20], low-pressure axial fans [21,22], and hollow blade axial fans [23,24]. Hu et al [25] conducted an FW-H acoustic simulation on high-speed axial flow fans, and the results showed that the noise on the blade pressure surface was greater than that on the suction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since the cooling fan is one type of axial fan, several investigations also have been concentrated on high-speed axial fans [17], low-speed axial fans [18][19][20], low-pressure axial fans [21,22], and hollow blade axial fans [23,24]. Hu et al [25] conducted an FW-H acoustic simulation on high-speed axial flow fans, and the results showed that the noise on the blade pressure surface was greater than that on the suction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Vortex shedding from streamlined bodies can be observed in the case of low-speed fans for instance. One of the most prominent noise sources of these fans originates from the so-called profile vortex shedding [3,4]. This phenomenon is still in the focus of current research, thus, the thorough description and understanding of it is desirable.…”
Section: Introduction and Objectivesmentioning
confidence: 99%